2014
DOI: 10.1007/s00426-014-0611-3
|View full text |Cite
|
Sign up to set email alerts
|

The reversal of perceptual and motor compatibility effects differs qualitatively between metacontrast and random-line masks

Abstract: In masked priming tasks, participants typically respond faster to compatible than to incompatible primes, an effect that has been dubbed as the positive compatibility effect (PCE). However, when the interval between the prime and the mask is relatively long, responses are faster to incompatible than to compatible primes. This inversion is called the negative compatibility effect (NCE). Two main origins of the NCE have been proposed. The objectupdating theory holds that when the masks share stimulus features wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…For instance, Sumner (2008) found that the NCE was not different between classical random-line masks and fully irrelevant masks. More recently, Atas, San Anton, and Cleeremans (2014) showed that the origin of the NCE obtained with random line masks was purely motor, which is consistent with the motor inhibitory account. This NCE was not correlated with the NCE obtained with metacontrast masks, which elicited strong perceptual object updating effects.…”
supporting
confidence: 64%
“…For instance, Sumner (2008) found that the NCE was not different between classical random-line masks and fully irrelevant masks. More recently, Atas, San Anton, and Cleeremans (2014) showed that the origin of the NCE obtained with random line masks was purely motor, which is consistent with the motor inhibitory account. This NCE was not correlated with the NCE obtained with metacontrast masks, which elicited strong perceptual object updating effects.…”
supporting
confidence: 64%
“…Therefore, Experiment 3 was carried out to compare conflict adaptation between different SOA and different prime duration conditions. Note that using arrow primes masked by metacontrast masks (or random-line masks) in combination with long mask–target SOAs (i.e., 100–150 ms) induces negative compatibility effects instead of positive compatibility effects (see, e.g., Atas, San Anton, & Cleeremans, 2014; Eimer & Schlaghecken, 2003; Lingnau & Vorberg, 2005; McBride, Boy, Husain, & Sumner, 2012). Therefore, we used random pixel masks, which have elicited positive compatibility effects even at a mask–target SOA of 100 ms in previous studies (Desender, Van Opstal, & Van den Bussche, 2014; Reuss, Desender, Kiesel, & Kunde, 2014; Verleger, JaĹ›kowski, Aydemir, van der Lubbe, & Groen, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Instead, the evaluation window model would suppose an abrupt shift from PCE to NCE depending on whether the evaluation window did or did not include the prime. Klauer and Dittrich (2010) addressed this limitation by suggesting that the NCE could be explained by multiple mechanisms, with the evaluation window being one of them; similarly, other authors (Atas et al, 2015) have also suggested that both object updating and self-inhibition could underlie the NCE. In a way, the neural habituation model is as a cohesive implementation of these different mechanisms, directly showing how the varied NCE results can be explained by the combination of perceptual and response priming.…”
Section: Relationship To Other Nce Theoriesmentioning
confidence: 99%